THE IMPROVEMENT OF SCHOOL PRINCIPAL’S SOCIAL COMPETENCE THROUGH GIVING REWARDS AT PUBLIC ELEMENTARY SCHOOLS OF KAMPAR KIRI TENGAH IN KAMPAR - Wismardi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The background of the research in this paper is the low social competence of School Principals at the Public Elementary Schools of Kampar Kiri Tengah sub-districts in Kampar. It can be seen from the initial survey conducted by the researchers. Most teachers, apparently, had not made collaboration either individually or in groups in improving schools. The type of research is School Action Research. Based on the results of the data presentation and discussion, it can be concluded that giving rewards can improve the social competence of School Principals at the Public Elementary Schools of Kampar Kiri Tengah sub-districts in Kampar. In terms of the aspect of giving rewards delivered by tutors, it is seen that from cycle I the score increased in cycle II. If in cycle I the percentage score was 74% and in cycle II it was subsequently higher by getting a percentage score of 86%. In the aspect of the School Principal’s social competence, the percentage score in the first cycle was 58.1% with the sufficient category and in the second cycle, it increased to 82.4% with the good category. It means that the improvement of the School Principal’s social competence through giving rewards at public elementary schools of Kampar Kiri Tengah sub-districts in Kampar is considered to be successful.